TANTANGAN MODERNISASI DALAM PENERAPAN SPIRITUAL HEALING MELALUI TERAPI SHOLAT DI ERA DIGITAL - Zakiyyah Darojah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The development of globalization and modernization has had a extensive effect on society, mainly in phrases of increasing individualism, materialism, and intense social competition. These phenomena often lead to anxiety, stress, and restlessness in individuals’ lives. In this context, spirituality becomes an important aspect that can provide inner peace and a sense of meaning in life. One form of spirituality in Islam is sholat (prayer), which is viewed as a means of communication between humans and Allah SWT, and has potential as a form of spiritual therapy. This study aims to examine sholat as a form of spiritual healing. The research employs a library research technique with a qualitative descriptive method. records were acquired from diverse literature assets, which incorporates books, articles, and journals. The findings suggest that sholat is not quality a religious responsibility however moreover a shape of spiritual treatment that could foster tranquility, peace, and inner happiness. Through khushu’ (devotion), tafakkur (reflection), tuma’ninah (serenity), and submission to Allah, sholat provides individuals with mental and emotional strength to face life’s pressures. Thus, sholat plays an important role as spiritual healing in addressing the challenges of modern society.